MUHAMMAD SA’ID AL-‘ASHMAWI (Mencabar Pemikirannya tentang Penerapan Syarî’ah di Mesir) - Moh. Hefni (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2009)
The rise of a vigorous and sometimes violent Islamistmovement in Egypt has attracted considerable attentionfrom scholars. Less attention has been given to those whohave responded to this challenge at the level of ideologicaldebate. One of these is a prominent judge, Muhammad Sa’idal-‘Ashmawi. He argues that the call for the "application ofthe syarî’ah" (tathbîq al-sharî’ah), watchwords of the Islamistmovement, are in reality little more than empty slogans,designed to get popular support for a political venture butextremely vague and probably insignificant in substance. Intime, however, its meaning expanded, first to include all ofthe rules for worship and society found in the Qur’ân, thenthose in the sunna of the Prophet, and finally all the opinionsand judgments of the scholars (ijtihâd). But these opinionsand judgments are properly called fiqh, and the final result ofthe development is that in common usage the term syarî’ahhas come to mean fiqh.Those who use the slogan, however,are in fact calling for the application oí fiqh, that is, a set ofrules and laws devised by humans, not God, to meethistorical conditions of the past which no longer obtain. Indiscussing ribä, al-cAshmawi holds that current Egyptianlaw essentially conforms to the syarî’ah. The same is true ofthe rest of Egyptian law.